Texture shaping in modern fashion design - Kisil, M. (Theory and practice of design, 2016)
The article deals with the texture that have formative properties. The study identified such texture as single cut, topstitch, in stitch and origami. The process of shaping garments was considered in the «concept of shaping —structure of form — texture».